THE STUDENTS’ PERCEPTIONS ON SELF-REFLECTION SHEET IN MICROTEACHING CLASS - Cut Mawar Helmanda (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2017)
Microteaching lesson has been implemented to train the student teachers to be able to deliver their teaching material. Most students feel the anxiety at the beginning of the lesson periode. To reduce this feeling, the lecturer ask the students to write down a single-paper self experience that they have got through their teaching simulation performace. This study was gained to get the information about students’ perceptions on self-reflection sheet in microteaching class. The opened-questionnaires sheet were shared by the writer to the students English teachers who studied microteaching lesson in sixth semesterin 2016-2017 academic year of Muhammadiyah Universiy Aceh. Here the writer wanted to know whether the self-reflection sheet gives the positive aspect or not. The sample of this study was random sampling. The subject of this research were 10 students from one unit microteaching. The subject described that the self-reflectin sheet gave them the drawn of what they felt and did during their performance, so that they could do better things in the next round teaching simulation and feel there was something positive happened. By having self-reflection sheet, the student teachers realized their weaknesses in their teaching performance.